CONSERVATION COCCINELLA SP. AS PREDATOR OF GREEN PEACH APHID MYZUS PERSICAE SULZER ON POTATO INTERCROPPING - Lamria Sidauruk (UNEJ e-Proceeding, 2016)
Green peach aphid, Myzus persicae (Sulzer), is the major pest on potato in Karo Highland, North Sumatera. This aphid also vector of Potato leafroll virus (PLRV) and Potato Virus Y (PVY). This study aims to determine the kind of plants intercropping to be applied with potato plant at organic farming system, in order to conservation Coccinella sp. as potenstial predator of Myzus persicae Sulzer. This study design by Split plot design with the main plot is farming systems (conventional and organic) and the subplot is the planting system (monoculture potato; potato-cabbage; potato-mustard; potato-celery; potato-cabbage-mustard; Potato-cabbage-celery; potato-mustard-celery; potato-cabbage-mustard-celery). The data was analyzed by ANOVA and Tukey test. Intercropping system potato-cabbage-mustard-celery, potato-cabbage-mustard, potato-mustard-celery and potato-mustard significantly increasing population of Coccinella sp. on potato field with organic farminf system. At the intercropping system found the lowest populations of M. persicae, and the highest crop production. Planting season February-April found the higher population of Coccinella sp. than planting season May-August on organic farming.